al-Makhṭūṭ al-ʻUmānī fī Aṣqāʻ al-Maʻmūrah - Bakhtah, ʻAzzūzī (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Heritage is necessary by every measure — not only to achieve continuity between the ages, nor only to realise the possibilities of progress, but to achieve identity and preserve the existence of the community alongside meeting the civilizational challenge it lives. Arabic manuscripts are among the most distinctive features of Arab-Islamic civilization and a civilizational and cultural inheritance that reached us from forebears who took to writing with unmatched devotion and were passionate in composition. Omani manuscripts formed part of this inheritance, which gives us a living picture of an intellectual production that flourished in the several fields of learning, thought and philosophy, and which is an important memory of the Arab community and a gateway to reading its history. Arabic manuscripts, and Omani manuscripts among them, have suffered damage and loss for natural and human reasons, including plunder and burning at the hands of the coloniser, and manuscripts passed into other countries — a dispersal this study traces.
MHF-PRINT2018-006
Keywords: Omani manuscripts; Cultural heritage; Manuscript dispersal; Arab-Islamic civilization; Preservation; Identity